Une prison pour mémoire Montluc, de 1944 à nos jours - André, Marc (Sociétés, Espaces, Temps, 2022)
How do traumatic but at times competitive memories, anchored in different wars and events, end up finding common ground to emerge as a shared narrative? How do we reconcile memory and history? Marc André locates the answers to these questions in the history of Montluc, a prison doubly marked by the violence that shook the twentieth century and the tumultuous memory battles that continue to rattle the twenty-first. Since 2010, when Montluc was converted into a national Memorial, the prison has remained in the crossfire of heated debates between those speaking for the survivors of the Nazi Occupation on the one side, and those speaking for the survivors of Montluc who had served time for their anticolonial politics during the Algerian War (1954-1962) on the other. André challenges the prevailing notion of competing memories by exploring the ways in which the multitude of prisoners, their experiences, and memories past and present, came to find resonance in Montluc, and even so after they were released. Following the liberation of the prison in 1944, Nazi criminals and collaborators who joined the militia were tried and imprisoned in Montluc at the same time as former members of the Resistance who had become vocal opponents of colonial oppression during the French-Indochina and Algerian Wars. At one point, a Communist militant was tried for his protest against the French-Indochina War and placed in the same cell as the one he had once occupied under Vichy. Victims of Klaus Barbie drew on their past experiences and memories while in Montluc to rally around the Algerians who were being rounded up, tortured, and ultimately guillotined on the prison grounds. When Montluc survivors gathered in front of plaques along the prison wall, in remembrance of Nazi victims, they came to see the ceremony as an occasion to denounce the wars of decolonization. These temporal collisions in and around Montluc would soon foster unexpected ties of solidarity between the many prisoners and survivors who had experienced different regimes of oppression across multiple wars. In this meticulously researched and thought-provoking book, André immerses us in Montluc, a space where the shadows cast by past events came to engage in constant dialogue. He brings to life the ensemble of experiences and narratives-in essence, the lives-that converged in Montluc to make it a prison for memories.